Metode Pembelajaran Rasulullah SAW (Telaah Kualitas Dan Makna Hadis) - Hardivizon, H (BELAJEA: Jurnal Pendidikan Islam, 2017)
This study aims to understand the hadith about learning method of Rasulullah SAW. The sides to be examined are on the historical dimension of the hadith of the prophet, from the start of descent to the study of maÄn al-á¸¥adÄ«á¹£. From these, created a historical concept of the hermeneutical map in the study of Islam and its relevance in the study of hadith, in order to get a more contextual and applicative meaning. This research approach is adopted from hermeneutic Hassan Hanafi in understanding the texts of revelation as a source of law. Namely, depart from three consciousness; 1) history (asy-syuâur at-tarikhy), 2) eidetis (asy-syuâur at-taâammuli) 3) praxis (asy-syuâur al-âamali). The study found: 1) In conveying the message through the lecture method, the Prophet conveyed with clear talk, easy to understand, and if necessary repeated three times. 2) Question-answer method used by the Prophet to invite curiosity of his friend, and also to provide teaching based on problems owned by his friend. 3) The experimental method is applied to applied sciences such as agriculture, with the aim of obtaining understanding after the experimental process. 4) Methods of demonstration he did to show the procedure of the implementation of something, such as tayammum. Companions can easily understand what he is showing, without needing to explain it verbally